Environmental Health Inspection and Targeted Food Safety Education at Three Nusantara Capital Authority Office Premises - Riyan Nigsih; Blego Sedionoto; Dwi Wilujeng Budiarti; Karolina Puspitasari; Yulis Tanty; Riana Embun Masiroh (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This community-service article reports hygiene and sanitation conditions identified through environmental health inspections and describes targeted food-safety feedback delivered at three food premises in the Nusantara Capital Authority office area, Indonesia.Research Methodology: This descriptive cross-sectional case series involved one snack outlet and two class-A1 restaurants. Compliance was assessed using Ministry of Health Regulation No. 17 of 2024 checklists, with scores calculated from applicable compliant items. Data were analyzed descriptively, and immediate educational feedback was provided during inspections.Results: Premises A, B, and C recorded 13/86, 25/225, and 23/225 nonconforming items, producing compliance scores of 84.88%, 88.89%, and 89.78%, respectively. Raw nonconformity counts were not directly compared because checklist denominators differed. Identified gaps concerned personal hygiene, protective clothing, nail cleanliness, covered waste bins, internal labeling, freezer arrangement, thawing procedures, kitchen temperature, fly control, training documentation, and annual health-examination records.Conclusions: The inspections identified premise-specific corrective priorities and enabled immediate, context-specific feedback. Findings were limited to the three inspected premises and cannot demonstrate intervention effectiveness, behavioral change, contamination, or wider regional compliance. Limitations: Limitations included a single inspection, no posteducation reassessment, microbiological or chemical testing, severity weighting, or inter-rater reliability assessment. Contribution: This article provides a transparent inspectionfeedback procedure for similar community-service activities, with appropriate local adaptation, current regulatory references, and follow-up evaluation.